Managerial economics - Maurice, S. Charles; Thomas, Christopher R. (Boston : Irwin/McGraw-Hill, 1999)
The objective of the book is to provide readers with a book that will enhance your learning experience in managerial economics. This sixth edition emphasize the economic way of thinking about business decision making. it has also been designed in such a way that it is easy to teach and learn managerial economics.
Includes index.
Includes index
nmn 13/10/17
Loan
Keywords: Managerial economics; Managerial decision making; Economics